Marine bacteria harbor the sulfonamide resistance gene sul4 without mobile genetic elements - Shindoh, Suzune; Kadoya, Aya; Kanechi, Reo; Watanabe, Kozo; Suzuki, Satoru (Frontiers in Microbiology, 2023)
Marine bacteria are possible reservoirs of antibiotic-resistance genes (ARGs) originating not only from clinical and terrestrial hot spots but also from the marine environment. We report here for the first time a higher rate of the sulfonamide-resistance gene sul4 in marine bacterial isolates compared with other sul genes. Among four sulfonamide-resistance genes (sul1, sul2, sul3, and sul4), sul4 was most abundant (45%) in 74 sulfonamide-resistant marine isolates by PCR screening. The order of abundance was sul4 (33 isolates) > sul2 (6 isolates) > sul3 (5 isolates) > sul1 (1 isolate). Whole-genome sequencing of 23 isolates of sul4-expressing α-and γ-Proteobacteria and Bacilli revealed that sul4 was not accompanied by known mobile genetic elements. This suggests that sul4 in these marine isolates is clonally transferred and not horizontally transferable. Folate metabolism genes formed a cluster with sul4, suggesting that the cluster area plays a role in folate metabolism, at which sul4 functions as a dihydropteroate synthase. Thus, sul4 might be expressed in marine species and function in folate synthesis, but it is not a transferable ARG.